2019
DOI: 10.1093/aob/mcz003
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive strategy in Dactylorhiza orchids: multidirectional evolution of floral chemistry

Abstract: Background and AimsThe deception strategies of orchids remain poorly understood, especially in regard to the chemical compounds emitted from their flowers and their interaction with various taxonomic groups of pollinators. We investigated the phylogenetic relationships and compared the variation of floral chemical compounds between food-deceptive Dactylorhiza taxa (D. incarnata var. incarnata and D. incarnata var. ochroleuca, D. fuchsii and D. majalis) from populations in north-eastern Poland. We propose a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 98 publications
1
13
0
Order By: Relevance
“…It may strengthen associative learning and thus encourage repeat visitation by pollinators (Knudsen & Gershenzon, 2006). Wróblewska et al (2019) reported that the floral chemical compounds in studied D. incarnata populations were dominated by aldehydes and n-alkanes/alkenes, and the benzoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may strengthen associative learning and thus encourage repeat visitation by pollinators (Knudsen & Gershenzon, 2006). Wróblewska et al (2019) reported that the floral chemical compounds in studied D. incarnata populations were dominated by aldehydes and n-alkanes/alkenes, and the benzoids.…”
Section: Discussionmentioning
confidence: 99%
“…The Dactylorhiza genus is recognized as food-deceptive orchids, and it has been used as a model for investigating plant-pollinator interactions, natural selection, and, consequent female reproductive success (Mattila & Kuitunen, 2000;Sletvold et al, 2010;Trunschke et al, 2017). The study of Wróblewska et al (2019)…”
Section: Introductionmentioning
confidence: 99%
“…The reason why A. mellifera and potentially other insects can be lured by D. majalis is the floral chemical compounds released by D. majalis, which were reported by Wróblewska et al (2019) in populations from north-eastern Poland. These chemical compounds include p-hydroxybenzyl alcohol (a volatile compound in Vanilla, describing it as vanilla-like), and aldehydes (which are important components of floral odor in the appetitive proboscis extension response in honey bees, Wang et al 2016), particularly nonanal.…”
Section: Discussionmentioning
confidence: 99%
“…This may depend on several aspects, including the extraction methods and the analytical tools chosen [ 20 , 254 , 255 ]. For instance, more polar compounds such as polyphenols are less volatiles and therefore the use of protic solvents (such as methanol, diethyl ether or water–ethanol) results in substantially different chemical characterizations in respect to dynamic headspace sorption methods (i.e., [ 176 , 185 , 192 ]). Individual situations also contribute to changing metabolic processes and thus varying phytochemical profiles.…”
Section: Phytochemical Information and Pharmacology Of European Orchidsmentioning
confidence: 99%